Integration of Augmented Reality in Natural Appearance Learning to Improve The Visual-Spatial Abilities of Elementary School Students - Nanis Regina Choerunnisa; Devi Afriyuni Yonanda; Eka Nurhidayat (Eduvest - Journal of Universal Studies, 2026)
This research aimed to investigated the effectiveness of a structured intervention program in enhancing spatial ability among twenty-one participants using a pretest-posttest design. Spatial ability was measured across four dimensions: Spatial Visualization, Spatial Orientation, Spatial Relations, and Mental Imagery. The intervention consisted of systematic training activities designed to develop multiple facets of spatial thinking. Results demonstrated substantial improvements in spatial ability following the intervention, with mean scores increasing from forty-eight point eight-nine at pretest to seventy-seven point four-six at posttest. This improvement represents a fifty-eight percent increase and yielded an exceptionally large effect size of four point three-eight, substantially exceeding the conventional threshold for large effects. The normalized gain analysis revealed a mean value of zero point five-six-five, classified as moderate effectiveness. Notably, the distribution of performance categories shifted dramatically, with all participants successfully transitioning from low to moderate or high performance levels. The paired samples t-test confirmed statistically significant differences between pretest and posttest scores. Improvements were balanced across all four spatial ability dimensions, ranging from fifty-two point nine percent to sixty-three point two percent, indicating that the intervention comprehensively addressed multiple aspects of spatial cognition rather than focusing narrowly on specific components. These findings provide robust evidence that spatial ability is a malleable cognitive competency that can be systematically developed through targeted instruction, with important implications for educational practice, particularly in STEM fields where spatial thinking is fundamental to success.